Decompressive hinge craniotomy as an alternative for low-resource settings - Ernesto Enrique Horta-Tamayo; Angel Jesus Lacerda-Gallardo (Revista Cubana de Medicina Militar)
Decompressive hinge craniotomy as an alternative for low-resource settings